VIDEO RESOLUTION ENHANCEMENT BY USING COMPLEX WAVELET TRANSFORM - Demirel, Hasan; Anbarjafari, Gholamreza; Ozcinar, Cagri; Izadpanahi, Sara (IEEE, 2011)
In this paper, we propose a multi-frame video resolution enhancement technique based on dual tree complex wavelet transform (DT-CWT). Here, before registration step, the respective frames have been passed through an illumination compensation procedure which is based on singular value decomposition (SVD) and discrete wavelet transform (DWT). The frame subject to the resolution enhancement is decomposed into its different frequency subbands by using DT-CWT. The high frequency subbands have been interpolated by using bicubic interpolation. Furthermore, the compensated frames are registered by using Vandewalle registration with structure adaptive normalized convolution reconstruction. Afterwards, the interpolated subbands and the output of the registration technique have been combined by using inverse DT-CWT (IDT-CWT) in order to reconstruct the super resolved frame. For Akiyo video sequence there is 5.04 dB, 4.86 dB, 5.22 dB, and 5.05 dB improvements in the average PSNR values compared to Vandewalle, Marcel, Lucchese, and Keren registration techniques, respectively.
18th IEEE International Conference on Image Processing (ICIP) -- SEP 11-14, 2011 -- Brussels, BELGIUM
Keywords: Image